Comparison of indirubin concentrations in indigo naturalis ointment for psoriasis treatment: a randomized, double‐blind, dosage‐controlled trial. (1st January 2018) - Lin, Y.‐K.; See, L.‐C.; Huang, Y.‐H.; Chi, C.‐C.; Hui, R.C.‐Y.
Summary: Corticosteroids are commonly used topical (applied to the skin) therapies in psoriasis; although beneficial, there are concerns about their prolonged use and there is a need for effective alternatives. Many herbal remedies have been used topically, although evidence for their benefit is often limited. Indigo naturalis has been used for several years in Chinese traditional medicine; unfortunately, when taken by mouth it can cause gastro‐intestinal side effects or liver damage. Previous studies have shown it may be effective, as a crude ointment or a refined preparation, containing the active ingredient indirubin, which causes less skin staining than the crude preparation. Indirubin has anti‐inflammatory properties and reduces the excessive turnover of cells called keratinocytes in the outermost layer of skin, the epidermis, which is seen in psoriasis. The authors, based in Taiwan, aimed to find the optimal concentration of indirubin in a topical preparation. They recruited 109 adults with psoriasis affecting less than 20% body surface area. The subjects received different concentrations of indirubin (ranging from 10 to 200 μg/g) for an 8 week treatment period, followed by a further 12 week monitoring period. The researchers measured the Psoriasis Area and Severity Index (PASI) before and after treatment, which is a measurement of how severe a person's psoriasis is. 200 μg/g was the most effective concentration: in this group 56.5% of patients achieved a 75% improvement and 30.4% a 90% improvement in PASI score, with a reduction of itching. The improvement was maintained after discontinuing treatment. No major side effects were observed, although skin irritation occurred in some patients, even on the lowest dose. Clearly this study needs confirmation, but the authors propose that topical indirubin is beneficial in psoriasis, with an efficacy between that of a topical medicine called calcipotriol and the combination of calcipotriol with a potent corticosteroid, but with less toxicity than the latter.